2022
DOI: 10.3390/life12040582
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Chondrocytes and Subchondral Bone in Osteoarthritis

Abstract: The aim of this review is to provide an updated review of the epigenetic factors involved in the onset and development of osteoarthritis (OA). OA is a prevalent degenerative joint disease characterized by chronic inflammation, ectopic bone formation within the joint, and physical and proteolytic cartilage degradation which result in chronic pain and loss of mobility. At present, no disease-modifying therapeutics exist for the prevention or treatment of the disease. Research has identified several OA risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 284 publications
0
6
0
Order By: Relevance
“…Virtual screening of potentially active constituents targeting DNMT1 from DD DNMT1-mediated hypermethylation of PPARγ promoter in chondrocytes is a key mechanism for promoting OA (Ball et al, 2022). To identify the active constituents of DD for the treatment of OA by targeting DNMT1, 906 constituents from DD were docked into the pocket for DNMT1.…”
Section: Results and Disussion Dd Alleviated Tibial Subchondral Bone ...mentioning
confidence: 99%
“…Virtual screening of potentially active constituents targeting DNMT1 from DD DNMT1-mediated hypermethylation of PPARγ promoter in chondrocytes is a key mechanism for promoting OA (Ball et al, 2022). To identify the active constituents of DD for the treatment of OA by targeting DNMT1, 906 constituents from DD were docked into the pocket for DNMT1.…”
Section: Results and Disussion Dd Alleviated Tibial Subchondral Bone ...mentioning
confidence: 99%
“…Osteoarthritis (OA) is a degenerative joint disease that results in cartilage damage and chronic pain and disability in those affected [66,67]. Known risk factors include age, obesity, traumatic or developmental joint instability, chronic inflammatory conditions, and modulation of epigenetic regulation [10,[68][69][70]. Studies have shown that inflammation plays a key role in the onset and progression of OA through increased expression of matrix proteases and stimulation of chondrocyte hypertrophy and apoptosis [15,71].…”
Section: Discussionmentioning
confidence: 99%
“…OA is a whole joint disease that results in chronic inflammation, cartilage degradation, abnormal subchondral bone remodeling, osteophyte formation, synovitis, and fibrosis of the infrapatellar fat pad [4][5][6][7][8]. Articular chondrocytes are the primary cell type present in cartilage and are responsible for secretion and homeostasis of an extracellular matrix (ECM) composed of collagen type-II-α (Col2α) and proteoglycans [9][10][11][12]. When damaged, chondrocytes are unable to repair the damage and contribute to degradation by undergoing cellular hypertrophy and apoptosis and increasing production of matrix-degrading proteases, such as matrix metalloproteinases (MMPs), responsible for breakdown of the collagenous and non-collagenous cartilage matrix components [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Primary OA is more prevalent and is a result of aging, whereas secondary OA is caused by joint trauma or other illness [3]. OA can be regarded as a multifactorial disease, with several factors including aging, genetic predisposition, epigenetic control, inflammation, obesity, and trauma being involved in its pathophysiology [4].…”
Section: Introductionmentioning
confidence: 99%